Uji Efektivitas Sediaan Emulgel Ekstrak Etanol 70% Daun Murbei (Morus alba L.) Sebagai Antiinflamasi - Rizaldi, Gusti; Wahyunita, Sari Wahyunita; Rahmiati, Nur (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Non-steroidal anti-inflammatory drugs (NSAIDs) commonly used have associated side effects, necessitating the search for safer alternatives based on natural ingredients. This study aims to evaluate the effectiveness of a 70% ethanol extract emulgel of mulberry leaves (Morus alba L.) as an anti-inflammatory agent. The methodology employed is an experimental study involving the formulation of emulgel, which was tested on Wistar rats. The extraction process utilized maceration of mulberry leaves with 70% ethanol, yielding a concentrated extract that was then formulated into an emulgel. Anti-inflammatory activity was assessed using carrageenan induction and measuring edema volume in the test animals. The results indicated that the mulberry leaf extract emulgel exhibited significant anti-inflammatory activity, with a p-value of <0.023, demonstrating a meaningful difference compared to the positive control. The formula with a concentration of 0.32% showed the best efficacy at 180 minutes. The conclusion of this study highlights the potential of the 70% ethanol extract emulgel of mulberry leaves as a safe and effective alternative for anti-inflammatory therapy, recommending further safety testing to ensure its safe use in the community.